PERENCANAAN CAMPURAN LATASIR (SAND SHEET) MENGGUNAKAN PASIR DAN ABU BATU EX. PT. DWI PERMATA KUARRY - Haris Haris (Jurnal Ilmiah Hospitality, 2022)
Construction of highway facilities will facilitate traffic flow and facilitate relations between regions, especially remote areas and urban areas. The importance of the highway as a means of land connection requires good road conditions, so that an alternative asphalt mixture is cheap and affordable. Mixing Latasir using sand stone ash and stone ash as a filler in the mixture is expected to gain flexibility. For that aggregate characteristics and mixture composition must meet specifications. The method used in this study uses trial and error namely by making several test specimens to be sampled. The method of research carried out is aggregate testing (sand stone ash and stone ash originating from PT. Dwi Permata Kuarry), asphalt testing and manufacturing specimens on asphalt mixtures with variations in asphalt content are 5.0%, 5.5%, 6.0%, 6.5% and 7.0%. Based on the results obtained from the aggregate sieve analysis data for the composition of Latasir mixture namely sand stone ash = 89.5% and ash filler stone = 10.5%. On the Marshall test results Latasir mixture between sand stone ash and stone ash PT. Dwi Permata Kuarry, VIM value (Void in Mix) ranged from 6.636% -2.165% and VFA (Void Filled with Asphalt) ranged from 15.969% -37.112% in the range of asphalt variations of 5.0% -7.0%.